Country Report: How do Serbian municipalities currently promote health and health equity?. (13th November 2019) - Karadzic, V; Jovanovic, D; Vasic, M
Abstract: A legal framework set in Serbia provide good basis for creating healthy living environment and health promotion at local level. The present system of local government in Serbia, with its 174 units is regulated by the Law on Local Self Government. In accordance to this Law each municipality has got a certain level of decision-making. Creating healthy living environment is one of the key objectives of municipal policy and its agenda. However, the extent of their inclusion and implementation is very heterogeneous between municipalities. Unequal municipalities' capacities (financial, technical, human resources) for coordination and development of healthy living environment on the municipality level are crucial challenge. In order to support the activities at the local level, the Network of 24 regional institutes of public health, led by the Institute of Public Health of Serbia, develops public health guidance, participate in drafting local strategies, programs and activities. Additional support is provided by the Local Health Councils, increasing a political sensibility for prioritizing issues to achieve healthy living environment. The coherent framework of mandates, local strategies and action plans for improving the public health have been established through widespread cooperation between the institutes of public health, health councils, and other stakeholders (e.g. nongovernmental organizations and governmental bodies such as the ministries responsible for education, environmental protection, youth and sport). In spite of that, their implementation is restricted by low awareness of importance of health equity and health promotion. In that sense, training and education on health promotion and health equity issues are crucial to raise the awareness, increase health literacy and enable satisfactory and quality implementation of defined strategies, programs and activities at the municipality level.